Differential regulation of the expression of aquaporins 3 and 9 by Auphen and dbcAMP in the SMMC-7721 hepatocellular carcinoma cell line. (3rd July 2016) - Peng, R; Zhang, Y; Zhao, GX; Li, J; Shen, XZ; Wang, JY; Sun, JY
Abstract : Aquaglycero-aquaporins (agAQPs) are the structural foundation of rapid water transport and they appear to participate in cancer proliferation and malignancy. AQP3 expression is increased and AQP9 expression is decreased in hepatocellular carcinoma (HCC) compared to normal liver, which suggests their possible use as targets for cancer treatment. AQP-based modifiers, such as Auphen and dibutyryladenosine 3′, 5′-cyclic monophosphate (dbcAMP), might be used to treat several diseases and as chemical tools for assessing the functions of AQPs in biological systems. We investigated the effects of both Auphen on AQP3 and dbcAMP on AQP9 in SMMC-7721 cells. We used western blotting, real-time quantitative polymerase chain reaction (qPCR) and immunohistochemistry to evaluate changes in AQP3 and AQP9 expression in SMMC-7721 cells after culturing with Auphen and dbcAMP, respectively. We also determined the proliferation of SMMC-7721 cells. We found that compared to HL-7702 (L02) liver cells, Auphen increased AQP3 expression in tumor cells, whereas dbcAMP decreased expression of AQP9 in these cells. Also, high concentrations of Auphen and dbcAMP inhibited proliferation of SMMC-7721 cells in vitro. Auphen and dbcAMP may inhibit HCC development and could be considered targets for HCC diagnosis and therapy.